Early Childhood Care in Sambas Muslim Family: Cultural and Religious Influences - Bayu Suratman; Nurjannah Nurjannah (Nadwa: Jurnal Pendidikan Islam, 2021)
This article reports an in-depth study on early childhood care in Sambas Malay Muslim family.  This research incorporated a qualitative method with a descriptive approach through observations and interviews with parents and Sambas local figures.  The findings indicate the influence of local culture and religious values on Sambas Muslim parenting style. More specifically, this study showed that parenting practices of Muslim Sambas Malay parents are carried out through the tradition of pantang larang and kemponan. Pantang larang and kemponan become parts of collective memory so that they become social educative traditions in early childhood care in the Muslim Sambas Malay family.